(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
This work tries to place to discussion the functions of the traditional doctors of the northern region of the State of Mexico. For this analysis, the specialist’s office to cure the disease known as fright is documented in the Otomí community of San Antonio Detiña, municipality of Acambay. It is guided by the ethnographic method and takes up the points of view of community actors: patients and traditional doctors, who interact at different times in the treatment of the disease. Sustaining that the validity of the traditional doctor’s offi ce is supported in the cosmovisions about the body, social relations and geographical space.